Cycloalkyl-substituted salicylaldimine-nickel(II) complexes as mediators in controlled radical polymerization of vinyl acetate - Silva, Talita T. [UNESP]; Silva, Yan F. [UNESP]; Machado, Antonio E. H.; Maia, Pedro Ivo S.; Tasso, Carlos R. B.; Lima-Neto, Benedito S.; Silva Sa, Jose L.; Carvalho-Jr, Valdemiro P. [UNESP]; Batista, Nouga C.; Goi, Beatriz E. [UNESP] (Taylor & Francis Inc, 2019)
Nickel(II) complexes of Schiff base derived from cycloalkylamines (cycloalkyl = cyclopentyl (cpen), cyclohexyl (chex), and cycloheptyl (chep)) were synthesized: [Ni-II(L-cpen)(2)] (1), [Ni-II(L-chex)(2)] (2), and [Ni-II(L-chep)(2)] (3). The Schiff base-Ni-II complexes 1-3 were characterized by FTIR, UV-Vis, elemental analysis, and computational methods. Electrodeposited films of complexes 1-3 were obtained by potential cycling CH2Cl2 on platinum electrode, and their electrochemical behavior were characterized by cyclic voltammetry. The polymerization of vinyl acetate (VAc) initiated by azobisisobutyronitrile (AIBN) at 55 degrees C were conducted according to an organometallic-mediated radical polymerization (OMRP) mechanism. The best conversions were obtained using a ratio of [VAc]/[AIBN]/[Ni] = 542/3.25/1, reaching 50, 69 and 85% in 12 h for 1, 2 and 3, respectively. The kinetic of polymerization mediated by complex 1 exhibited a linear dependence of ln([VAc](0)/[VAc]) versus time, supporting a constant radical concentration; while for the complexes 2 and 3, the radical concentration was constant for a short period of time. The increase of molecular weights with the conversion coupled with low polydispersities indicate a certain level of control of the polymerization when using the complexes [Ni-II(L (R))(2)] as controlling agents.
Keywords: OMRP; Schiff base; nickel complexes; vinyl acetate; polyVAc